2005
DOI: 10.1097/01.ccm.0000151047.33912.a3
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting transfusion practices in critically ill patients*

Abstract: Canadian physicians appear to have adopted lower transfusion triggers and an increase in the use of single-unit red cell transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 19 publications
4
56
1
Order By: Relevance
“…Research has shown that smoking directly leads to alterations in platelet membranes and causes impairment of their natural function [13,35,38], therefore it seemed plausible to us that there would be an association between smoking and blood loss after spinal surgery. Should that be the case, it would be a modifiable risk factor that potentially could help patients avoid the neurologic compli cations of bleeding after spine surgery (such as development of a compressive hematoma), and the known deleterious effects of transfusions [15,16,20,32,40,42,43,45,52]. Our results suggest that smoking is strongly associated with increased surgical blood loss and perioperative transfusions in patients undergoing lumbar spine surgery.…”
Section: Discussionmentioning
confidence: 67%
“…Research has shown that smoking directly leads to alterations in platelet membranes and causes impairment of their natural function [13,35,38], therefore it seemed plausible to us that there would be an association between smoking and blood loss after spinal surgery. Should that be the case, it would be a modifiable risk factor that potentially could help patients avoid the neurologic compli cations of bleeding after spine surgery (such as development of a compressive hematoma), and the known deleterious effects of transfusions [15,16,20,32,40,42,43,45,52]. Our results suggest that smoking is strongly associated with increased surgical blood loss and perioperative transfusions in patients undergoing lumbar spine surgery.…”
Section: Discussionmentioning
confidence: 67%
“…First, the response rate to our questionnaire was 43%. While this response rate is within the range of other recently published surveys of critical care professionals [37][38][39][40], our study could certainly be limited by sampling bias. Regarding the potential for sampling bias, the large proportion of female questionnaire-recipients (95%), and respondents (94%), is consistent with existing data showing that 96% of United States SLPs are female [14].…”
Section: Discussionmentioning
confidence: 86%
“…Since this study, pre-hospital trauma care, 30 surgical management of trauma, 54 and intensive care staffing 55 have all evolved, and Canadian physicians have adopted a more conservative approach to red blood cell transfusion in critically ill patients. 56 However, the trend to declining injury-related deaths in Canada during the study period may be due to prevention initiatives rather than to advances in the care of trauma patients. 2 In addition, the evidence base, attitudes, beliefs, and practices for transfusion in acute trauma resuscitation are not wellcharacterized.…”
Section: Discussionmentioning
confidence: 99%